Rapid progression of a low-grade follicular lymphoma with foci of high proliferation index and BCL6 rearrangement into a diffuse large B-cell lymphoma: A case report and review of the literature - Simran Kalsi, BS; Steven Gersen, PhD; Ronald Harris, DO; Jagmohan S. Sidhu, MD (Elsevier, 2019)
Follicular lymphoma (FL) is a common type of non-Hodgkin lymphoma, characterized by the translocation t(14;18) IGH/BCL2 that usually runs an indolent course. It has been known to transform into diffuse large B-cell lymphoma (DLBCL). While the exact mechanism of this transformation is unknown, several contributing genetic changes have been identified. We present a case study of a 74-year-old male who presented with right side flank pain and inguinal lymphadenopathy. The patient was diagnosed with low-grade follicular B-cell lymphoma with a low proliferative index (LGFL-LPI) and focal high proliferation index. Approximately 6 months later, the patient was diagnosed with LGFL-HPI with evidence of transformation into DLBCL of activated B-cell immunophenotype within the same lymph node. Separate fluorescence in situ hybridization (FISH) studies performed on the initial biopsy, the low grade component of the subsequent sample, and the transformed component of the subsequent sample were identical, revealing BCL2 and BCL6 gene rearrangements without MYC rearrangement in all components. As BCL6 rearrangement in a FL has been reported as a harbinger of transformation of FL into DLBCL, we believe that the short timeframe of transformation in our case may be attributed to the presence of BCL6 rearrangement in combination with the high proliferation index. This phenomenon of rapid transformation of FL into DLBCL with presence of a combination of BCL6 gene rearrangement and high proliferation index in both lymphomas has not been previously reported to our knowledge. We suggest that the presence of a combination of BCL6 rearrangement and high proliferation index could be an important prognostic factor, and its role in rapid progression of FL should be further investigated in larger studies. Keywords: Low-grade follicular lymphoma, Diffuse large B-cell lymphoma, BCL6 rearrangement, IGH/BCL2 rearrangement, LGFL-HPI